Teenage Pregnancies and Births in Germany: Patterns and Developments - Kamila Cygan-Rehm; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2014)
We study the development of teenage fertility in East and West Germany using data from the German Socioeconomic Panel (SOEP) and from the German Mikrozensus. Following the international literature we derive hypotheses on the patterns of teenage fertility and test whether they are relevant in the German case. We find that teenage fertility is associated with teenage age and education, with the income of the teenager's family, with migration status, residence in East Germany, and aggregate unemployment. Our evidence supports countercyclical teenage fertility.
Keywords: J13; Z18; I00; 330; teenage fertility; abortion; unemployment; East and West Germany; population economics